Mechanism of Oxidation of Paracetamol by Bromamine-B in Acid Medium: A Kinetic Approach - Vaz, Nirmala; Puttaswamy (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of paracetamol (PAM) by sodium N-bromobenzenesulfonamide (bromamine-B or BAB) in HClO4 medium has been studied at 303 K. The reaction is of first-order in [BAB] and of fractional-order each with respect to [PAM] and [H+]. The variation of ionic strength and the addition of the reaction product, benzenesulfonamide, and halide ions had no significant effect on the reaction rate. Decrease in dielectric constant of medium increases the rate and the solvent isotope effect was studied using D2O. The rates were determined at different temperatures and the activation parameters for the overall reaction have been computed. Michaelis-Menten type of kinetics is observed and activation parameters for the rate-limiting step have also been computed. 4-Amino-2,6-dibromophenol was identified as the oxidation product of PAM. Mechanism (scheme) consistent with the observed kinetic data has been proposed and discussed.